To study the prevalence of tuberculosis in children of sputum positive adult of pulmonary tuberculosis living in same household - Beck, P.; K. Kurrey, Virendra; Dawale, Prafull (International Journal of Medical Research and Review, 2015)
Introduction: Mortality due to tuberculosis can be prevented with proper screening, diagnosis and treatment. Present study is proposed to propagate screening of all children in families of all adult with sputum positive for AFB by relevant test available locally. This will help in early detection childhood infection. Objective of this study was to identify the prevalence of tuberculosis in children of sputum positive adult of pulmonary tuberculosis living in same household. If the findings are statistically significant routine screening should be recommended as part of RNTCP. Method: Prospective, hospital plus community based study during a period of February 20013 to November 20014, inclusion criteria includes all children 5-14 year, should have contact with sputum positive adult, exclusion criteria - children who treated with antitubercular, TB with concurrent immunosupression, Detail history, clinical examination, and investigation done to find out tubercular infection or disease. Result: We observed that among 218 children 40% children had tubercular infection out of which 23 children had tubercular disease. Data of different parameter is observed and analyzed which is found statistically significant. Conclusion: This study argue strongly in favours of routine screening of all children in contact with sputum positive adult of PTB and identify this group of child at high risk who should be screened on a priority basis if there of resources and time to screen all family contact.